Analysis of the main parameters of spring and summer food compound of roe deer (Capreolus capreolus L.) on the two hunting grounds of the Alföld plain - Barta, Tamás; Majzinger, István (Acta Agraria Debreceniensis, 2010)
It is widespread that roe deer are very choosy. It needs this sorting because the micro organisms, which help the digestion of high fibre plants, are missing in its stomach that is why they are mostly called „concentrate selectors” (Hoffmann, 1985, 1988, 1989). These animals should mostly eat easily digestible plants with high nutrition level (pulses, buds, sprouts and flowers), and they are able to do this sorting because of their small mouth size. In winter there is a lack of these plants, so the high selectivity occurs only when the feed is in abundance. Examining the amount and quality of vegetation available on the habitat of roe deer we can identify the species which can satisfy their feed demand. It is known, that roe deer as other large ruminants, from the plant abundance prefer certain plants and plant parts while there are others which are avoided. The identification of the eaten species and the rate of their occurrence in the feed is the first step to become acquainted with the interaction between animal and the surroundings.